Mechanical and Physical Properties of Low Density Kenaf Core Particleboards Bonded with Different Resins - Saad, Mohamad Jani; Kamal, Izran (Journal of Science and Technology, 2012)
Single layer kenaf (Hibiscus cannabinus) core particleboards bonded with urea formaldehyde (UF), phenol formaldehyde (PF) and polymeric 4,4-methyl phenylmethane di-isocyanate (PMDI) resins were manufactured. The boards were fabricated with three different densities i.e 350 kg/m3, 450 kg/m3 and 550 kg/m3. Each type of the resin used was sprayed at three different resin loadings on the kenaf core particles. The boards produced was evaluated for its modulus of rupture (MOR), modulus of elasticity (MOE), internal bond (IB), screw withdrawal (SWD), water absorption (WA) and thickness swelling (TS) in accordance with the British Standards. The study revealed that boards with higher resin contents gave higher MOR, MOE, internal bond and screw withdrawal and also improved the water absorption and thickness swelling. Similar trend was also observed from boards with higher densities. It is concluded that the boards with the density of 550 kg/m3 were able to fulfill the British Standard specifications.